Race in translation : culture wars around the postcolonial Atlantic - Stam, Robert, 1941-; Shohat, Ella, 1959- (New York University Press, 2012)
While the term "culture wars" often designates the heated arguments in the English-speaking world spiralling around race, the canon, and affirmative action, in fact these discussions have raged in multiple sites and languages. Charting the multidirectional traffic of the debates, Stam/Shohat trace their literal and figurative translation, seen in French Postcolonial Studies and Brazilian Whiteness Studies, and in such cultural phenomena as Tropicalia and Hip-Hop. The authors also interrogate an ironic convergence whereby rightist politicians join hands with leftist intellectuals, along with th